2015
DOI: 10.1021/acs.jmedchem.5b00893
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into the Interactions between Death-Associated Protein Kinase 1 and Natural Flavonoids

Abstract: Death-associated protein kinase 1 (DAPK1) is a 160 kDa serine/threonine protein kinase that belongs to the Ca(2+)/calmodulin-dependent protein kinase subfamily. DAPK1 is a possible target for the treatment of acute ischemic stroke and endometrial adenocarcinomas. In the present study, we investigated the binding characteristics of 17 natural flavonoids to DAPK1 using a 1-anilinonaphthalene-8-sulfonic acid competitive binding assay and revealed that morin was the strongest binder among the selected compounds. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 44 publications
1
70
0
1
Order By: Relevance
“…The catalytic domain of the DAPK1 protein (residues 1-285) was prepared using an Escherichia coli system as described previously (Yokoyama et al, 2015). The purity was assessed by SDS-PAGE with Coomassie Brilliant Blue (CBB) staining and was estimated to be greater than 90%.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The catalytic domain of the DAPK1 protein (residues 1-285) was prepared using an Escherichia coli system as described previously (Yokoyama et al, 2015). The purity was assessed by SDS-PAGE with Coomassie Brilliant Blue (CBB) staining and was estimated to be greater than 90%.…”
Section: Methodsmentioning
confidence: 99%
“…Wilbek and coworkers identified an imidazopyramidazine compound (CPR005231) as a DAPK1 inhibitor with a K d of 0.24 mM (Wilbek et al, 2015). In addition, during the course of our research on the interaction of DAPK1 with natural flavonoids, we found that several natural flavonoids bind to DAPK1 with different binding affinities via various binding modes, and that the binding affinities can be drastically modulated by a slight change of the functional group (Yokoyama et al, 2015). These results led us to the idea that a DAPK1 inhibitor might be discovered among anthraquinone derivatives, including emodin and quinalizarin.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…We also evaluated the interaction between compound 1 and DAPK1 (5AUT.pdb) 16 using molecular modeling docking studies (Figure 6C and D). Since compound 1 activates/stimulates DAPK1, we posited that ATP would be in the ATP binding pocket and allosterically modulate it.…”
mentioning
confidence: 99%